THE DIDACTIC ASPECTS OF INFORMATION AND COMMUNICATION TECHNOLOGIES IN TEACHING THE TECHNICAL SUBJECTS - KUTNA, Anna; PALASTHY, Hedviga (Journal of Technology and Information Education, 2009)
The development of the science and technology in particular invariably provoked extreme pressure on all education systems. The growing discrepancy between the amount of knowledge that man has to cope with limited time and opportunities to their adoption. It is necessary to modernize the content and design education. The schools usually respond conservatively, slowly and carefully. New thinking has placed increased demands on permanent self-educators. The aim of the contribution is to remit to the importance of information and communication technologies in teaching the subject of computer networks at the Department of Informatics, Pedagogical Faculty, Catholic University in Ruzomberok. The contribution presents the distance education, the preparation of electronic teaching materials and tests in Moodle system, the demonstration of sample chapter, which discusses various aspects such as architecture, management, and security models.
Keywords: e-learning; ICT; didactic aspects; computer networks